2010
DOI: 10.2174/187152710793361522
|View full text |Cite
|
Sign up to set email alerts
|

Opioid Regulation of Mu Receptor Internalisation: Relevance to the Development of Tolerance and Dependence

Abstract: Internalisation of the mu opioid receptor from the surface of cells is generally achieved by receptor occupancy with agonist ligands of high efficacy. However, in many situations the potent analgesic morphine fails to promote internalisation effectively and whether there is a direct link between this and the propensity for the sustained use of morphine to result in both tolerance and dependence has been studied intensely.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 68 publications
2
11
0
Order By: Relevance
“…Previous studies have shown that opioid receptors are [3,32,33] . After chronic or acute exposure to morphine, activated neurons and glia exhibit increased expression of pro-infl ammatory cytokines, such as TNF-α, IL-1β, IL-6 [19,34,35] , and chemokines [36,37] .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies have shown that opioid receptors are [3,32,33] . After chronic or acute exposure to morphine, activated neurons and glia exhibit increased expression of pro-infl ammatory cytokines, such as TNF-α, IL-1β, IL-6 [19,34,35] , and chemokines [36,37] .…”
Section: Discussionmentioning
confidence: 97%
“…At the cellular level, morphine exerts its effects via G protein-coupled receptors, primarily μ-opioid receptors, resulting in the activation of intracellular signal-transduction kinases [3] . Nuclear factor-κB (NF-κB) is one of the most diverse and critical transcription factors that may either directly or indirectly transmit opioid receptor-mediated signals to the nucleus, and it regulates NF-κB-dependent gene expression in immune and non-immune cells [4] .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Morphine realize it analgesic function trough targeting μ opioid receptor (MOR). Desensitization and trafficking of μ opioid receptor has been widely accepted as a main reason for morphine tolerance [3941]. By regulating such transcription factors of OPRM (MOR gene) as NF-κB through different pathways, miR-93 and Smad5 may participate in the formation of morphine tolerance [36, 42].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, during chronic opiate use, the brain adapts, restricting the effects of opiates by internalization of opiate receptors. 36 This idea is supported by behavioral findings, demonstrating better executive functioning and visuospatial abilities in the patients who received long-term methadone treatment (6 months) compared to the patients receiving shortterm treatment (30 days). 37 …”
Section: Higher Bold Response During Spatial Working Memory Task In Tmentioning
confidence: 80%